MODEL LOG-LINEAR FAKTOR-FAKTOR YANG MEMPENGARUHI HIPERTENSI (STUDI KASUS: RSUD ABDOE RAHEM SITUBONDO) - KAMIL, IMAMUDDIN; SUSILAWATI, MADE; NILA KENCANA, I PUTU EKA (E-Jurnal Matematika; Volume 1, No 1, Tahun 2012, 2012)
The purpose of this study was to determine the effect of the factors age, sex, obesity, family history (heredity), and smoking habits on hypertension status. The research data is secondary data obtained from the medical records of disease in hospitals in East Java Abdoe Rahem Situbondo the data of patients affected by hypertension stage I and II, with a sample size of 137 patients. Methods of data analysis using log-linear regression analysis. The result showed the best log-linear Model are: log m ijklmn = U + U 134(ikl) + U 245(jlm) + U 456(lmn) + U 1246(ijln) + U 12356(ijkmn) , explained the factors that influence the risk of hypertension (U6), namely the factors that can not be changed such as gender ( (U 1 ) , age ( (U 2 ), family history ( (U 3 ), while factors can be changed such as smoking habits ( (U 4 ), and obesity ( (U 5 ). Interactions also occur between the factors that influence the risk of hypertension, as shown in the model U 134(ikl) , namely gender, family history, and smoking habits. In the model U 245(jlm) the factors age, smoking, and obesity among interacting factors that influence the risk of hypertension.
Keywords: Log-linear models; best log-linear model; the factors of hypertension